Biopsy-derived oral keratinocytes – A model to potentially test for oral mucosa radiation sensitivity. (May 2022) - Thomsen, A.R.; Aldrian, C.; Luka, B.; Hornhardt, S.; Gomolka, M.; Moertl, S.; Hess, J.; Zitzelsberger, H.; Heider, T.; Schlueter, N.; Rau, S.; Monroy Ordonez, B.; et al.
Highlights: Human oral keratinocytes – the key players in radiation mucositis in head and neck cancer treatment – are established ex vivo from patient-derived micro-biopsies. Individual radiosensitivity of primary oral keratinocytes is measured by a novel assay for cellular proliferation and spreading. The keratinocyte model also supports classical functional assays such as clonogenic survival and DNA double strand repair. Abstract: Purpose: To establish stable in vitro growth of keratinocytes from very small biopsy specimens and successfully apply new test systems to determine their radiosensitivity. Materials and Methods: Oral mucosa biopsies (diameter: 1.7 mm) from 15 subjects were immobilized with custom-made cups onto culture plates. Outgrowing cells were tested for cytokeratin 5/14 and Ki67, expanded, radiated at different doses, and seeded onto circumscribed areas before being allowed to spread centrifugally. In this newly developed spreading assay, cell-covered areas were measured by image analysis. For statistical analysis, a linear mixed regression model was used; additionally, results were correlated to the radiation dose applied. Colony forming efficiency (CFE) was used to validate the results. DNA damage repair was analysed by gammaH2AX and 53BP1 foci quantification using immunofluorescence microscopy 24 h and 96 h after irradiation. Results: Stable keratinocyte growth continued for up to 7 weeks in 14 biopsies. Cells spread reliably from an initial 16.6 mm 2 up to a median of 119.2 mm 2 (range: 54.4–290). Radiated cells spread to only 100.7 mm 2 (2 Gy; range: 55.3–266.7); 73.2 mm 2 (4 Gy; 15–240.4); 47 mm 2 (6 Gy; 2–111.9), and 22.7 mm 2 (8 Gy; 0–80). Similarly, CFE decreased from 0.223 (0 Gy) to 0.0028 (8 Gy). Using an individual donor as a random factor, cell spread correlated with CFE, where radiation dose was the main driver (decrease by 0.50, adjusted for area). Upon irradiation with 6 Gy, radiation-induced DNA damage was increased after 24 h in all samples, and even after 96 h in 5 out of 7 samples, as detected by a higher number of gammaH2AX/53BP1 foci in irradiated cells (mean 3.7 for 24 h; mean 0.6 for 96 h). Conclusion: In vitro propagation of keratinocytes derived from a small biopsy is feasible. Radiation impairs cellular migration and proliferation, and the newly described spreading assay allows ranking for cellular radioresistance. The keratinocyte model also supports classical functional assays such as clonogenic survival and DNA double strand repair. The clinical relevance awaits upcoming investigations.